PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN PATI KABUPATEN PATI (Jurnal Mahasiswa Pasca Sarjana, 2013)
This aims of this study is to examine the effect of job’s motivation, teacher’s competence and the leadership’s of Headmaster on teacher’s performance of Senior High School Teachers in Pati District. The Specific objective of this study is to examine the role of the Headmaster to moderates the influence of job’s motivation and teacher’s competence on teacher’s performance. The benefit of this study is to describe and extend previous study of the role of the Headmaster to moderate the influence of job’s motivation and teacher’s competence on teacher’s performance.This study used a sample of state junior high school teachers in Pati District. They are 90 teachers from 274 teachers. Sampling in this study is a nonprobability sampling with purposive sampling method, by taking data from teachers who meet the specific criteria of the overall population.Based on the results of the study can be summarized as follows: job’s motivation to work had no effect on teacher’s performance, teacher’s competence had a significant and positive effect on teacher;s performance, the principal's leadership does not influence on the performance of teachers, the principal's leadership does not moderate the effect of job’s motivation on teacher’s performance, the leadership of the headmaster strengthen the influences of teachers' competence on teacher’s performance. Keywords: motivation, competence of teachers, school leadership and teacher’s performance